Commercial Bombus impatiens colonies function as ecological traps for wild queens. Issue 4 (5th February 2023) - Miller, Olivia; Hale, Casey; Richardson, Leeah; Sossa, David; Iverson, Aaron; McArt, Scott; Poveda, Katja; Grab, Heather
Abstract: In response to anthropogenic environmental change, the cues that animals use throughout their lifecycle to optimize fitness may become unreliable, resulting in an ecological trap. Here we investigated whether commercial bumble bee Bombus impatiens colonies managed for early spring crop pollination act as ecological traps for wild nest‐searching Bombus queens by subverting their natural nest usurpation behaviour. An average of 10 dead wild queens were recovered from each standard colony during the 2‐week period of the experiment, but colonies with queen excluders were successful in preventing wild queen deaths. The use of queen excluders did not impact colony performance in terms of resident queen survival, colony reproduction, colony weight gain or worker body size. Sites where wild nest‐searching queens were small had higher rates of failed usurpation, suggesting smaller‐sized queens are disproportionately at risk from failed usurpation. Furthermore, sites where commercial colonies without queen excluders were introduced for spring crop pollination had fewer bumble bee visits to a later‐blooming crop compared to sites without commercial colonies. Synthesis and applications . Our findings reveal a novel mechanism by which commercial colonies can negatively impact wild bumble bee populations and their pollination services. At the same time, we demonstrate a simple and inexpensive risk mitigation tool—a queen excluder—was 100% effective at eliminating this risk without compromising colony performance. Commercial colonies used outdoors during the bumble bee nest‐searching period should be fit with queen excluders to prevent negative impacts on wild pollinator communities and their services. Abstract : Our findings reveal a novel mechanism by which commercial colonies can negatively impact wild bumble bee populations and their pollination services. At the same time, we demonstrate a simple and inexpensive risk mitigation tool—a queen excluder—was 100% effective at eliminating this risk without compromising colony performance. Commercial colonies used outdoors during the bumble bee nest‐searching period should be fit with queen excluders to prevent negative impacts on wild pollinator communities and their services.